2017
DOI: 10.1007/s00586-017-5320-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of prognostic factors predicting survival in patients with spinal bone metastases

Abstract: Results After screening, 142 full-text articles were obtained, of which 22 met the eligibility criteria. A total of 43 different prognostic factors were investigated in the included studies, of which 17 were relevant to pre-treatment survival estimation. The prognostic factors most frequently associated with survival were the primary tumor and the performance status. The prognostic factors most frequently not associated with survival were age, gender, number and location of the SBM and the presence of a pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
(20 reference statements)
5
14
0
1
Order By: Relevance
“…This may not only be due to the patients’ oncologic outcome, but may also reflect the influence of other age-prevalent causes such as cardiovascular diseases. As reported by many studies before, we also found that the performance status was a strong prognostic factor for predicting the residual life expectancy after palliative RT of SBM in elderly patients [2327]. Here, patients with a KPS below 70% had an extremely poor overall survival of less than 2 months compared to 9 months for those patients with a KPS of at least 70%.…”
Section: Discussionsupporting
confidence: 75%
“…This may not only be due to the patients’ oncologic outcome, but may also reflect the influence of other age-prevalent causes such as cardiovascular diseases. As reported by many studies before, we also found that the performance status was a strong prognostic factor for predicting the residual life expectancy after palliative RT of SBM in elderly patients [2327]. Here, patients with a KPS below 70% had an extremely poor overall survival of less than 2 months compared to 9 months for those patients with a KPS of at least 70%.…”
Section: Discussionsupporting
confidence: 75%
“…It is crucial to identify factors that serve as prognosticators for increased survival, as only patients with a life expectancy of at least 3-6 months may experience the bone-mineralizing and stabilizing effects of palliative RT. Consistent with the findings of several other studies [28,36,[40][41][42], we identified the performance status as a strong prognostic factor for predicting OS after RT. As recalcification of irradiated osteolytic SBM usually takes up to several months, it is unlikely that patients with KPS < 70% would have a benefit with regard to stabilization within the remaining lifespan.…”
Section: Discussionsupporting
confidence: 91%
“…A recent systematic review. suggested that prognostication for patients with spinal metastases should be based on an accurate primary tumor classification, combined with a performance score, in which the added benefit of visceral metastases and other possible predictive factors should be studied further [19]. In our study brain and visceral metastases were significantly associated with survival, with an HR of 3.8 for brain metastases and HR of 1.34 for visceral metastases.…”
Section: Discussionmentioning
confidence: 53%